The transition experience of rural older persons with advanced cancer and their families: a grounded theory study - Duggleby, Wendy D (BioMed Central, 2010)
BACKGROUND: Transitions often occur suddenly and can be traumatic to both patients with advanced disease and their families. The purpose of this study was to explore the transition experience of older rural persons with advanced cancer and their families from the perspective of palliative home care patients, bereaved family caregivers, and health care professionals. The specific aims were to: (1) describe the experience of significant transitions experienced by older rural persons who were receiving palliative home care and their families and (2) develop a substantive theory of transitions in this population. METHODS: Using a grounded theory approach, 27 open-ended individual audio-taped interviews were conducted with six older rural persons with advanced cancer and 10 bereaved family caregivers. Four focus group interviews were conducted with 12 palliative care health care professionals. All interviews were transcribed verbatim, coded, and analyzed using Charmaz's constructivist grounded theory approach. RESULTS: Within a rural context of isolation, lack of information and limited accessibility to services, and values of individuality and community connectedness, older rural palliative patients and their families experienced multiple complex transitions in environment, roles/relationships, activities of daily living, and physical and mental health. Transitions disrupted the lives of palliative patients and their caregivers, resulting in distress and uncertainty. Rural palliative patients and their families adapted to transitions through the processes of "Navigating Unknown Waters". This tentative theory includes processes of coming to terms with their situation, connecting, and redefining normal. Timely communication, provision of information and support networks facilitated the processes. CONCLUSION: The emerging theory provides a foundation for future research. Significant transitions identified in this study may serve as a focus for improving delivery of palliative and end of life care in rural areas. Improved understanding of the transitions experienced by advanced cancer palliative care patients and their families, as well as the psychological processes involved in adapting to the transitions, will help health care providers address the unique needs of this vulnerable population.